Language Variations in Netizens' Comments on the News of the Jambret Sleman Case - Alien Kurnia Warya Selia; Achmad Dicky Romadhan; Safynatul Fawziyyah; Muhammad Salaebing (Universitas Negeri Semarang, 2026)
The development of the internet and social media has turned online news comment sections into digital public spaces where netizens express opinions, emotions, and social attitudes toward current events. This phenomenon is evident in news coverage of a mugging case in Sleman, which triggered diverse linguistic responses from digital users. This study aims to describe language variation in netizens’ comments on the Sleman mugging news, with a particular focus on code-switching and code-mixing, and to explain the social functions of these language choices. The study employs a qualitative descriptive approach, using comments from selected online news reports collected through purposive sampling. Data were gathered through observation and documentation techniques, then analyzed through reduction, classification, interpretation, and sociolinguistic presentation. The findings indicate that netizens’ comments exhibit diverse language variations, including informal registers, local languages, code-switching, and code-mixing. These language choices are used to emphasize attitudes, express emotions, build solidarity, and strengthen speakers’ social identities in digital space. This study contributes to the development of digital sociolinguistics and provides insight into linguistic dynamics in public responses to criminal news in online media.